Predicting the future of investor sentiment with social media in stock exchange investments: A basic framework for the DAX performance index - Lugmayr, Artur (2013)
© Springer-Verlag Berlin Heidelberg 2013. Recently much attention has been paid on initial public offerings of social media companies, such as Facebook or Linkedln and how their owners become millionaires. However, this paper does clearly not focus on the valuation of IPOs of social media companies! Stock markets are sentiment driven—the herd-like behaviour of investors lead easily to overreactions and investment decisions based on emotions. Within the scope of this article the power of social media as a tool for sentiment analysis for stock exchange investments is investigated. With the emergence of behavioural economics and finance and socionomic theories of finance, also today’s social media will provide implications on stock exchange market sentiments and investment decisions. This paper provides a framework how social media can be utilized as a tool for the evaluation of stock exchange market sentiments and which impact they have on particular investment decisions. News and information are the keys for successful investments, and social media provide an additional source of decision making, investment planning, or allow the spreading of financial news even quicker than news tickers. Within the scope of this paper, a framework for the application of social media as a tool in stock exchange trading is presented. The paper examines the potentials of social media for the analysis of themed focused social media platforms, collective mood analysis, attitude of investors and traders, social media content analysis, and the actual stock exchange value.